Climate Adaptation in Rain-fed Agriculture: Analyzing the Determinants of Supplemental Irrigation Practices in Nepal - Joshi, Ganesh Raj; Bhandari, Ramchandra (Research on World Agricultural Economy, 2022)
Climate change has severely impacted the rain-fed agricultural production system which is dominant in Nepal. This situation demands implementable strategies like supplemental irrigation for mitigating adverse impacts. In spite of the importance of supplemental irrigation, it is not adopted on a wider scale. Hence, this paper aims to assess perceptions of climate change and identify factors that influence the adoption of supplemental irrigation practices. Climate change impact survey data for Province No. 1 (one of the seven provinces in Nepal) with a sample of 800 households were analyzed by using the probit regression model. The results showed that the majority of the farmers perceived increasing temperature and decreasing precipitation, resulting in climate-induced disasters such as drought. Similarly, only about 27% of the households have adopted supplemental irrigation practices. The significant factors influencing the adoption of supplemental irrigation practices were the household head’s number of years of farming experience and education level, distance to motorable roads, operational size of landholding, membership in community-based organizations, and the perception of changes in summer temperature. Considering the empirical results, it is necessary to undertake research on sustainable practices and develop support measures for scaling up this practice as the adoption of this practice is very low in Province No. 1. The policy and strategy should also emphasize enhancing the capacity of farmers in technical and managerial aspects of supplemental irrigation practices, raising awareness about climate change and its impact, and strengthening community-based organizations for sharing and exchanging knowledge and skills. In addition, creating additional employment opportunities to enhance the income of the farmers for mitigating the capital constraint and increasing investment in infrastructures like roads for improving physical access thereby promoting adoption. ER